Systemic coordination through numeraires: initial simulation results - Garrido, Paulo (2017)
This paper presents initial results on the development of a paradigm for the coordination of large multi-agent systems abstracted from social coordination processes using money. We recall basic concepts and report on the development of a simulator for modeled systems. We present a “toy” example together with the determination and simulation of a steady-state for it. Next, we show results of perturbing the system parameters and the initial values of state variables in the steady-state. We conclude by reviewing the presented results, sketching a roadmap for development and considering the paradigm in a wider theoretical control perspective.